Severe Alcohol Intoxication in Canadian Adolescents: 2 Year Surveillance Data. (1st June 2016) - Acker, A; Dow, K; Norris, M; Allain, D; Thomas, K
Abstract: BACKGROUND: Alcohol is the most commonly used drug by Canadian adolescents, and can lead to a host of negative short and long-term outcomes. Understanding more about youth drinking can help develop more effective strategies for treatment and prevention. This study, gathering data through the Canadian Pediatric Surveillance Program (CPSP), was completed to fill in knowledge gaps and provide epidemiologic data about severe alcohol intoxication among Canadian adolescents. OBJECTIVES: The objectives of the surveillance study included: 1) To obtain national epidemiological data outlining the incidence of severe alcohol intoxication among adolescents. 2) To describe the demographics, presentation to hospital, co-ingestions, co-morbidities, management and short-term outcomes. 3) To use the data to increase awareness and education. 4) To facilitate harm reduction strategies. DESIGN/METHODS: Through the established methodology of the CPSP, paediatric physicians have been actively surveyed on a monthly basis for identified cases of severe alcohol intoxication. A detailed questionnaire was then completed for each new case. The case definition includes any adolescent meeting the following criteria: 1) Between 11-15 years of age 2) Blood alcohol level > 0 g/L (if drawn) 3) Presenting with severe intoxication with impaired consciousness requiring prolonged ER observation (≥ 6 hours) or hospital admission. RESULTS: In the two years of surveillance, 40 cases were confirmed, including 21 male and 19 female adolescents, with a median age of 14. The youngest case reported was 11 years old. There were no significant differences between sex and blood alcohol level or age at presentation and blood alcohol level. Additional descriptive data of the confirmed cases will be reported and discussed. CONCLUSION: After two years of surveillance, 40 cases of severe intoxication in adolescents have been identified. This is likely only the 'tip of the iceberg' and represents the more severe cases that required prolonged ER observation or hospital admission. The young age of presentation (youngest 11 years of age) and severity of intoxication requiring observation/admission are concerning. These data regarding Canadian adolescents presenting to the ED with severe intoxication will help inform strategies for education, prevention and harm reduction. It is noteworthy that the majority of adolescents with severe intoxication consumed spirits, suggesting that more education for adolescents around the higher potency of spirits relative to other alcoholic beverages and the dangers of consumption even in small amounts could reduce the incidence of severe alcohol intoxication in children and adolescents. Consideration of more stringent controls on spirits to help decrease adolescents' access would assist with harm reduction.